Data for the characterization of the HSP70 family during osmotic stress in banana, a non-model crop - Vanhove, A.C.; Vermaelen, W.; Cenci, A.; Swennen, Rony L.; Carpentier, Sebastien C. (Elsevier, 2015)
Data is presented from an in-depth analysis of the HSP70 family in the non-model banana during osmotic stress [1]. First, a manual curation of HSP70 sequences from the banana genome was performed and updated on the Musa hub http://banana-genome.cirad.fr/. These curated protein sequences were then introduced into our in-house Mascot database for an in-depth look at the HSP70 protein profiles in banana meristem cultures and roots during osmotic stress. A 2D-DIGE LC MS/MS approach was chosen to identify and quantify the different paralogs and allelic variants in the HSP70 spots.